Enzymatic Synthesis of DNA Complementary to Purified 14S Messenger RNA of Immunoglobulin Light Chain - Diggelmann, H. (1973)
The 14S messenger RNA, which contains poly(adenylic acid), of MOPC 41 (mouse plasmocytoma) immunoglobulin light chain, purified to a single peak as shown by polyacrylamide gel electrophoresis, was used to synthesize complementary DNA with the RNA-dependent DNA polymerase of avian myeloblastosis virus. DNA synthesis is entirely dependent on added RNA template and oligo(dT) primer. Both the size and the concentration of the primer affect the reaction. The product behaves similarly to DNA during centrifugation in cesium sulfate density gradients. It is shown by hybridization that the DNA made is complementary to the purified template, light-chain mRNA. The high specific activity of the complementary DNA should make it suitable for gene-dosage experiments. According to alkaline sucrose gradient analyses, some complete complementary DNA transcripts of the 14S mRNA seem to be made. Oligo(dG) can also function as a primer for DNA synthesis, possibly by annealing to an internal cluster of cytidines in the mRNA, that correspond to the bases coding for amino-acids 119 and 120 of the MOPC 41 light chain.